2018
DOI: 10.1002/tafs.10050
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Factors Influencing Somatic Growth of Lake Sturgeon

Abstract: Variation in somatic growth of Lake Sturgeon Acipenser fulvescens has primarily been attributed to temperature (latitude), but recent studies have suggested additional complexities. Based on populations in Manitoba, Canada, a multivariate analysis was conducted to reevaluate the extrinsic factors influencing growth of Lake Sturgeon. Length at ages 3, 6, 9, and 12 and the following six explanatory variables were examined: latitude, mean annual air temperature, pH, conductivity, juvenile Lake Sturgeon density (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 86 publications
(285 reference statements)
0
21
0
Order By: Relevance
“…Several studies (Fortin et al 1996;Power and McKinley 1997;Vélez-Espino and Koops 2009) attributed declines in condition and growth of Lake Sturgeon to lower mean annual air temperature, higher latitudes, and lower alkaline and conductive waters. McDougall et al (2018) suggested that temperature may be less important, but instead Lake Sturgeon density, habitat, and conductivity were more important. Although Lake Superior is not at the northern extent of Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Fortin et al 1996;Power and McKinley 1997;Vélez-Espino and Koops 2009) attributed declines in condition and growth of Lake Sturgeon to lower mean annual air temperature, higher latitudes, and lower alkaline and conductive waters. McDougall et al (2018) suggested that temperature may be less important, but instead Lake Sturgeon density, habitat, and conductivity were more important. Although Lake Superior is not at the northern extent of Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…The suite of mesh sizes used (25.4, 50.8, 76.2, 120.0 and 152.4 mm stretched measure) targets lake sturgeon measuring from 200 to 800 mm in approximate proportion to their abundance. McDougall et al () prescribes sampling deepwater habitat, wherever it exists, along the flow axis downstream of potential spawning areas, recognizing that reaches may differ in terms of juvenile lake sturgeon abundance, density, and growth (Barth & Anderson, ; McDougall, Nelson, & Barth, ). In the lower Seine River, field crews targeted areas where water depth exceeded 6 m, expected to harbour the majority of juvenile lake sturgeon within the system.…”
Section: Methodsmentioning
confidence: 99%
“…A power curve was fit to length‐at‐age data using the combined 2015 and 2016 data. Given that sampling was conducted in fall, seasonal growth potential was accounted for by assigning decimal ages based on capture dates (see McDougall et al, ). From the resulting power curve, length‐at‐age 3, 6, and 9 was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…2009; McDougall et al. ; Steffensen and Hamel ) as well as to ascertain information on habitat use and movement (Veinott and Evans ; Arai et al. ; Allen et al.…”
mentioning
confidence: 99%
“…Unlike otoliths, fin rays can be removed nonlethally, making them attractive for assessing at-risk populations (Collins and Smith 1996;Bruch et al 2009;Wolff et al 2013). As such, fin rays are commonly removed from sturgeon species to assess age and growth (Cuerrier 1951;Rien and Beamesderfer 1994;Bruch 1999;Parsons et al 2003;Koch et al 2008;Bruch et al 2009;McDougall et al 2018;Steffensen and Hamel 2018) as well as to ascertain information on habitat use and movement (Veinott and Evans 1999;Arai et al 2002;Allen et al 2009Allen et al , 2018bPhelps et al 2012Phelps et al , 2017Pracheil et al 2014Pracheil et al , 2019. Fin rays are the structural components of fish fins and are primarily composed of calcium phosphate (Ca 3 [PO 4 ] 2 ) mineralized as hydroxyapatite (Tzadik et al 2017a).…”
mentioning
confidence: 99%